2018
DOI: 10.2399/ana.18.074
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid attenuates iron-overload-induced structural changes in the liver of the laboratory mouse (Mus musculus)

Abstract: Objectives: The role of alpha-lipoic acid in the amelioration of iron overload-induced hepatic damage remains largely underexplored. Therefore, this paper aimed at describing the structural effects of alpha-lipoic acid on the liver following iron overload in mice. Methods: After ethical approval, a total of 24 male mice were used. Twenty mice were randomly divided into two groups: A and B. Group A rats received 50 mg/kg of iron dextran intraperitoneally daily for 49 days, while those in Group B received a dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Histopathological examination is regarded as the gold standard in assessing tissue injury 32 . Our findings for histopathological observation were consistent with other studies showing different models of iron overload 5,10,23 . The liver sections of iron overloaded rats showed swelling, cytoplasmic vacuolation, apoptosis, enlarged nuclei, and hepatocytes' fatty degeneration, which is considered one of the most detrimental results of oxidative damage to lipids hepatic parenchyma 33 .…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Histopathological examination is regarded as the gold standard in assessing tissue injury 32 . Our findings for histopathological observation were consistent with other studies showing different models of iron overload 5,10,23 . The liver sections of iron overloaded rats showed swelling, cytoplasmic vacuolation, apoptosis, enlarged nuclei, and hepatocytes' fatty degeneration, which is considered one of the most detrimental results of oxidative damage to lipids hepatic parenchyma 33 .…”
supporting
confidence: 93%
“…The liver is the major site for storing iron 23 . Therefore, it is considered the key organ to be adversely affected by iron overload toxicity 10 . Accumulating evidence showed that Angiotensin II is implicated in the progression of hepatic injury through induction of oxidative stress 15, 16 .…”
Section: Fig 3: Effect Of Lisinopril On Liver Enzymes Activity Alt As...mentioning
confidence: 99%
See 1 more Smart Citation